Status of drinking water, sanitation facilities, and hygiene in West Bengal: evidence from the National Family Health Survey of India (NFHS), 2019–2021 - Chandan Roy; Vishwambhar Prasad Sati; Amit Biswas; Saurav Kumar (Journal of Water, Sanitation and Hygiene for Development, 2023)
Access to safe drinking water and sanitation are essential fundamental rights for every citizen of a country. It is an important indicator of quality of life. Inadequate access to WASH services harms children under five and adolescent girls. This study examines the status of WASH services in West Bengal. A comprehensive assessment of WASH services was conducted using data from the fifth round of the National Family Health Survey. Data were statistically analyzed using Stata V. 14.1 software. A multivariate ordinal logistic regression model was applied to examine the association between experimental and explanatory variables. Furthermore, adjusted odds ratios, significance levels, and confidence intervals were provided for each dummy variable. The study found that only 33.69% of households in West Bengal have access to improved sources of drinking water. Moreover, only 74.35% of households have access to hygienic sanitation facilities within their premises, while 14.60% still practice open defecation. However, urban, Pucca, and non-nuclear households have better access to clean water, sanitation, and hygiene. The study also reported that drainage facilities are lacking in the state. Finally, the study recommends some policy measures to improve the access of WASH services in the state. HIGHLIGHTS People in non-nuclear households in cities have better access to WASH services.; Kolkata is ranked top in combined WASH services.; Purulia is the worst-performing district in terms of WASH services.; West Bengal's rural residents continue to practice open defecation.; The prevalence of diarrhea among children is higher in rural areas.;